Sexuality, student mental health nurse and lecturer experience in education and practice. (2nd November 2021) - Milward, Benjamin; Collier, Elizabeth
Abstract : This article presents a critical reflection on an experience relating to sexuality from two perspectives, a mental health nursing student and a lecturer. It took place during stage 1 of a graduate entry nursing 2-year Master of Science mental health nursing programme at a UK university. Student mental health nurses in higher education who identify as lesbian, gay, bisexual or transgender can feel less safe than others, which affects performance. Lecturers can make a difference to the educational experience of student nurses who are lesbian, gay, bisexual or transgender and this can have an impact on clinical practice. The emotional impact of 'coming out' in the classroom can have far-reaching consequences for their mental health. The response of educational staff can have a huge impact on the ability to learn and the marks achieved. Student–lecturer relationships can have transformative consequences. Student mental health nurses make meaning from their educational experiences in the classroom and clinical practice. If they do not see themselves represented, this can affect engagement and motivation. Safe nursing practice is role modelled from lecturer to student and has implications for service user experience in clinical settings.